ANALISIS PERBEDAAN BIAYA RIIL DENGAN TARIF INA-CBG’s DAN FAKTOR YANG MEMPENGARUHINYA UNTUK CHRONIC KIDNEY DISEASE PADA ERA JAMINAN KESEHATAN NASIONAL - Hadi Sulistyaningrum, Indriyati; Santoso, Arifin; Binarti (Sultan Agung Islamic University of Semarang, 2022)
Background: The National Social Security System (SJSN) is a system in the health sector that aims to provide comprehensive social security in order to create a just, prosperous and prosperous society. According to WHO growth in the number of Chronic Kidney Disease in 2013 increased by 50% from 2012 even in Southeast Asia to the number of sufferers of Chronic Kidney Disease> 380 million people. While in Indonesia, it has increased by 10% every year. This study aims to determine the differences between INA-CBG rates and the real costs of JKN-era Chronic Kidney Disease patients in RSISA Semarang. Method: This research is an observational study with a retrospective analytic descriptive design with quantitative data. The method used is the Cross Sectional method that makes observations, and can describe the factors that influence the real cost of hospitals. The population was 589 patients with Chronic Kidney Disease and 238 patients and analyzed using the chi-square statistical test with p-value <0.05. Results: The results of the study that as many as 14 patients (5.9%) aged 18-28 years, as many as 50 patients (21.0%) aged 29-39 years, as many as 82 patients (34.5%) aged 40-50 years , as many as 68 patients (28.6%) aged 51-60 years, as many as 21 patients (8.8%) aged 61-70 years as many as 3 patients (1.3%) aged 71-80 years. The research results obtained a p-value of 0,000. Conclusion: There is a Difference between Hospital Real Costs and INA-CBG's Rates for Chronic Kidney Disease in JKN Era in Semarang Hospital in 2018. There are no factors that affect the real costs in chronic kidney disease patients JKN participants in 2018 both class of care, length of treatment (LOS), and disease severity.